ADVANCE DIRECTIVES IN ROMANIA AND LITHUANIA - MOISĂ, Ştefana Maria; ENACHE, Angela Mariana; PÂRVU, Andrada; DUMITRAȘ, Silvia; GRAMMA, Rodica; ROMAN, Gabriel; IOAN, Beatrice (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Advance directives, a set of written instructions that a person gives that specify what actions should be taken for their health if they are no longer able to make decisions due to illness or incapacity, are a well-implemented tool in America, but few European countries have specific provisions about them in the law. Significant differences exist regarding the way advance directives are regulated and implemented between countries. The authors analyze the attitudes of several professional categories in Romania and Lithuania towards the advance directive using data obtained by conducting several interviews in Lithuania and a focus group in Romania. Both Romania and Lithuania are post-communist, now European Union member countries. All respondents thought that advance directives should be introduced in the law, but their social acceptance is expected to be low in Lithuania.